Clinical outcomes 1 year after empiric 131I therapy for hyperthyroid disorders: real life experience and predictive factors of functional response. Issue 9 (September 2017) - Vija Racaru, Lavinia; Fontan, Charlotte; Bauriaud-Mallet, Mathilde; Brillouet, Séverine; Caselles, Olivier; Zerdoud, Slimane; Bastié, Delphine; Vallot, Delphine; Caron, Philippe; Bardiès, Manuel; Courbon, Frederic
Abstract : Radioiodine is a therapeutic option in Europe for Graves' disease (GD) and toxic multinodular goiter (MNG). Purpose: To compare empiric and calculated 131 I activities using 2013 EANM recommendations. To look for predictive factors of therapeutic response to an empiric activity of 131 I. To assess clinical situations favoring calculated treatment modalities. Patients and methods: Prospective monocentric study of clinical outcomes at 1 year follow-up in 86 patients with GD and MNG who received empiric 131 I therapeutic activities (348–939 MBq). Differences between empiric and calculated activities were confronted to clinical outcomes. Physicians were not aware of the calculated activity at the time of prescription. Results: One year after treatment, 9% (5/57) of GD patients and 7% (2/29) of MNG patients were still in a hyperthyroid state. Thyroid volume was reduced by 67% for GD and by 50% for MNG. In GD, empiric 131 I activities were higher than calculated ones (564±131 vs. 316±319 MBq, P <0.001) in 93% (53/57) of patients. Pretherapeutic thyroid volume (>26 ml for GD; >40 ml for MNG) was associated with persistent hyperthyroidism. Conclusion: Empirically administered 131 I for GD and MNG was associated with very high efficacy in thyroid function control and no side effects. Thyroid volume reduction did not preclude treatment efficacy. Activity calculation could be a useful method for treating patients with GD and thyroid volumes higher than 26 ml or patients with MNG and thyroid volumes higher than 40 ml. A selective approach based on pretherapeutic thyroid volume and radioiodine biokinetics might improve treatment success. Abstract : Supplemental Digital Content is available in the text.